Preparation method of Bi2Fe4O9 material with strong ferromagnetism at room temperature

By introducing NaBH4 into Bi2Fe4O9 material for high-temperature calcination, Bi vacancy was induced, spin resistance was broken, and the strong ferromagneticity of Bi2Fe4O9 material was successfully achieved at room temperature, solving the problem of insufficient magnetic properties of existing materials, and providing new possibilities for photocatalytic recovery.

CN119797437APending Publication Date: 2025-04-11LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510081622.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing Bi2Fe4O9 materials exhibit paramagnetic or weak ferromagnetic at room temperature, making it difficult to achieve macroscopic magnetism, and magnetic recovery is difficult after photocatalysis.

Method used

By introducing NaBH4 for high-temperature calcination, Bi vacancy in Bi2Fe4O9 was induced, spin-hindshot was broken, and Bi2Fe4O9 nanomaterial with strong ferromagneticity at room temperature was successfully prepared.

Benefits of technology

The strong ferromagneticity of Bi2Fe4O9 material at room temperature was achieved, with the magnetization intensity reaching MS=10.22 emu/g and the residual magnetization intensity Mr=2.93 emu/g, which has the possibility of magnetic recovery after photocatalysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797437A_ABST
    Figure CN119797437A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Bi2Fe4O9 material with strong ferromagnetism at room temperature, Bi2Fe4O9 nanosheets are prepared by a hydrothermal method, then NaBH4 is introduced for high-temperature calcination, strong ferromagnetism of the material at room temperature is successfully induced, MS is equal to 10.22 emu / g, and Mr is equal to 2.93 emu / g. The strong ferromagnetism of the material at room temperature is found for the first time, and the possibility of further improvement exists. Meanwhile, ferroelectric hysteresis loop data shows that the sample still keeps ferroelectricity at room temperature. X-ray diffraction shows that all samples are single-phase, and no impurity is detected. Bi vacancies are inferred, based on a series of characterization analyses, to be a possible source that results in ferromagnetic. The interesting phenomenon of strong ferromagnetism Bi2Fe4O9 is never reported before, the new discovery can improve the magnetic cognition of people on the material, and meanwhile a new thought is provided for research of multiferroic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a strong ferromagnetic Bi2Fe4O9 material at room temperature, belonging to the technical field of functional material preparation. Background Art

[0002] Since the magnetoelectric coupling effect was predicted by P. Curie in 1894, people have been committed to finding materials that have both ferromagnetism and ferroelectricity at room temperature, namely multiferroic materials. Because it is possible to manipulate electrical and magnetic properties at the same time, it has great application potential in spintronic devices, sensors and digital storage devices. In the 1960s, people discovered weak magnetoelectric coupling in Cr2O3. In the following decades, the search for multiferroic materials encountered many difficulties and no significant progress was made. From the perspective of symmetry, ferromagnetism is expressed as time reversal symmetry breaking, and ferroelectricity is expressed as space inversion symmetry breaking. From the perspective of solid energy bands, ferromagnetic order requires a small band gap in the material, while ferroelectric order requires a large band gap. Because the mechanisms of ferromagnetism and ferroelectricity in materials are different or even conflicting, for a long time, not only have materials with coexistence of ferromagnetism and ferroelectricity not been found, but even materials with coexistence of antiferromagnetism and ferroelectricity are very rare. It was not until 2003 that the discovery of epitaxial BiFeO3 multiferroic thin film heterostructures brought about a revival in this field.

[0003] As a material that possesses both antiferromagnetism and ferroelectricity at room temperature, BiFeO3 has attracted a lot of attention recently. As a byproduct of BiFeO3 production, Bi2Fe4O9 also possesses multiferroic and photocatalytic properties near room temperature, but it has not attracted much attention and is little known.

[0004] For a long time, Bi2Fe4O9 has been considered to be an antiferromagnetic material at low temperature (264K±3) and paramagnetic material at room temperature, and has good photocatalytic performance. In order to facilitate the electrical and magnetic manipulation of the material and the magnetic recovery after photocatalysis, people have tried to change its magnetic properties by doping and compounding, and have obtained a slight improvement in its ferromagnetism at room temperature, but most of them are difficult to achieve macroscopic magnetism at room temperature or often contain magnetic impurities. Summary of the invention

[0005] In view of this, the present invention aims to disclose a method for preparing a Bi2Fe4O9 material with strong ferromagnetism at room temperature, by introducing NaBH4 for high temperature calcination, successfully inducing strong ferromagnetism of Bi2Fe4O9 at room temperature, wherein M S =10.22 emu / g, M r =2.93 emu / g.

[0006] 1. Preparation of strong ferromagnetic Bi2Fe4O9 materials 1) Preparation of Bi2Fe4O9 nanosheets: Bi(NO3) •5H2O and FeCl3•6H2O were dissolved in ethylene glycol solution, deionized water was added and mixed, and the pH was adjusted to 11.0±0.2 with concentrated ammonia solution. After complete precipitation, the precipitate was washed to neutrality and 13~15 mol / L NaOH solution was added and stirred evenly until no lumps were left. After hydrothermal treatment at 170~190℃ for 48~72h, the precipitate was acid washed to remove impurities, washed and dried to obtain Bi2Fe4O9 nanosheets, named BFO; wherein the molar ratio of Bi(NO3) •5H2O and FeCl3•6H2O is 0.75~0.85:1, and the volume ratio of ethylene glycol solution to deionized water is 1:3~1:5.

[0007] 2) Bi2Fe4O9 modification: Grind and mix BFO and NaBH4 evenly, put them into a porcelain boat, and then heat them to 300-400℃ in a tubular furnace with argon gas and calcine them for 1-2 hours. Then, pickle the obtained sample to remove impurities, wash and dry it to obtain modified Bi2Fe4O9 material; wherein the molar ratio of BFO to NaBH4 is 1:1-1:1.5.

[0008] For the convenience of experimental comparison, the molar ratio of BFO to NaBH4 was 1:1, and the samples obtained at 300℃ and 400℃ were named BFO-1 and BFO-2 respectively; the molar ratio of BFO to NaBH4 was 1:1.5. The sample obtained at 400℃ was named BFO-3, and the sample that was not washed with nitric acid after calcination was named BFO-3a. Under the same experimental conditions, the sample without adding NaBH4 was named BFO-3b.

[0009] The synthesis mechanism of the present invention: After synthesizing Bi2Fe4O9 nanosheets, NaBH4 was innovatively introduced for high-temperature calcination. By inducing Bi vacancies in Bi2Fe4O9, the spin frustration inside the Bi2Fe4O9 structure was broken, and Bi2Fe4O9 nanomaterials with strong ferromagnetism at room temperature were successfully prepared.

[0010] 2. Structural characterization and performance evaluation of strong ferromagnetic Bi2Fe4O9 materials 1. X-ray diffraction Figure 1This is the XRD spectrum of the modified Bi2Fe4O9 material prepared by the present invention. The results show that all the crystal diffraction peaks of the sample after calcination are consistent with PDF#25-0090, space group Pbam55, and there are no impurity peaks, which indicates that the sample is pure and the high-temperature calcination does not change the crystal structure of the BFO nanosheets. The sample is still pure single-phase Bi2Fe4O9. It is worth noting that under the same experimental conditions, the sample BFO-3a that was not washed with nitric acid after calcination has a peak value of 27.23 o , 38.03 o , 39.73 o and 31.88 o , 32.79 o , 46.23 o Bi (PDF#01-0699) and Bi2O3 (PDF#29-0236) were found in the BFO-3b without NaBH4 under the same experimental conditions, which proved that the introduction of NaBH4 led to the generation of Bi and Bi2O3. Since Bi powder is easily oxidized to Bi2O3 in air, it can be inferred that NaBH4 induced the precipitation of Bi from BFO, thus generating Bi vacancies.

[0011] 2. SEM characterization The microstructure of the samples was observed by SEM. Figure 2 , BFO presents a square flake shape, and a large number of porous bubbles appear on the surface of BFO-3 after calcination, but the overall morphology does not change significantly.

[0012] 3. XPS spectrum X-ray photoelectron spectroscopy (XPS) was used to identify the valence state of the sample surface to reveal the surface details before and after the reaction ( Figure 3 ), in the Fe2p spectrum ( Figure 3 a), Fe 2p at 710.8 eV 3 / 2 The peaks were deconvoluted to obtain two peaks at 711.3 eV and 710.1 eV, which belong to Fe 3+ and Fe 2+ , which indicates that there are both Fe 3+ and Fe 2+ , Fe 2+ The presence of is due to the inevitable oxygen deficiency during the sample preparation process. The percentages in the figure correspond to Fe 2+ The content of Fe 2+ The content of Fe is very small, and Fe 3+ and Fe 2+The content of O1s has not changed significantly. The deconvolution of O1s peak is 529.9 eV, 531.6 eV, and 533 eV, which are respectively attributed to lattice oxygen O L , oxygen vacancy O V , adsorb water or adsorb oxygen O H2O ( Figure 3 b), the percentages in the figure correspond to O V The amount of oxygen vacancies is obviously increasing gradually. According to the precipitation of Bi observed in XRD and the principle of electrical neutrality, the behavior of anion reduction after the reduction of cation Bi is predictable. Figure 3 c, 159 eV and 164.3 eV are respectively Bi4f 7 / 2 and Bi4f 5 / 2 There is no obvious change before and after the reaction.

[0013] Then, the element XPS peak spectra of different samples were semi-quantitatively analyzed and compared as shown in Table 1. The results showed that the relative content of Bi element gradually decreased, which was consistent with the results obtained by XRD.

[0014] Table 1 Semi-quantitative analysis of the element contents of BFO, BFO-1, BFO-2 and BFO-3 in XPS spectra 4. Raman scattering spectrum The Raman scattering spectra of BFO and BFO-3 samples were measured at room temperature. According to the irreducible statement of group theory, the orthorhombic Bi2Fe4O9 compound has 42 Raman active modes (12A g +12B 1g +9B 2g +9B 3g ), due to the small polarizability of some modes, the intensity is insufficient, so we capture fewer characteristic peaks, which is similar to previous observations. Figure 4 b The Raman spectra of both samples show typical Bi2Fe4O9 Raman characteristic peaks. Table 2 gives the specific Raman modes corresponding to the samples.

[0015] Table 2 Raman modes corresponding to characteristic peaks in BFO and BFO-3 In BFO, 61 cm -1 、79 cm -1 、110 cm -1 The active mode at 198 cm -1 The vibration of Fe1 tetrahedron is at 279 cm -1 、316 cm -1、416 cm -1 and 539 cm -1 The mode at 61 cm is attributed to the vibration of Fe2 octahedron. However, for BFO-3, no 61 cm -1 , 110 cm -1 The characteristic peaks of 208 cm-1 further prove the absence of Bi atoms in the structure. In addition, we found that all characteristic peaks are red-shifted to the left, which indicates the overall distortion of the lattice. -1 The characteristic peak of Fe1 is abnormally blue-shifted, and the Raman mode there corresponds to the atomic motion of Fe1 in the xy plane.

[0016] For Bi2Fe4O9 structure Figure 4 a, Fe1 atoms are antiferromagnetically coupled, Fe2 atoms are ferromagnetically coupled, and these Fe atoms have five main magnetic superexchange interactions in the crystal structure, from J1 to J5. The projections of J3 to J5 along the c-axis form a distorted pentagonal Cairo lattice (( Figure 4 c), there is strong spin frustration as a whole, which is the fundamental reason why Bi2Fe4O9 usually does not show macroscopic ferromagnetism at room temperature. o , and thus the strongest superexchange interaction in the lattice. Based on the large blue shift of Fe1 atoms in the Raman spectrum, this abnormal phenomenon may be the reason why Fe1 atoms break the Cairo pentagon spin frustration, leading to the macroscopic magnetism of BFO-3.

[0017] 5. Ferromagnetic properties The ferromagnetic properties of different samples were measured using VSM in the magnetic field strength range of ±2T at room temperature ( Figure 5 a), the results show that the BFO samples exhibit paramagnetism, as previously reported, while the calcined samples show obvious ferromagnetic hysteresis loops. The ferromagnetic properties increase with increasing calcination temperature and NaBH4 content, with the maximum saturation magnetization of BFO-3 being M S = 10.22 emu / g, and is almost saturated at a magnetic field strength of about 0.25 T. The residual magnetization intensity is M r =2.93 emu / g, coercivity HC = 221.5 Oe( Figure 5 b), it is foreseeable that the ferromagnetic properties may be further enhanced with the further increase of calcination temperature and NaBH4 amount. According to our research, such strong ferromagnetic properties of this material have never been reported before.

[0018] In addition, the PE curve of sample BFO-3 was obtained at room temperature and 1 kHz frequency. Figure 6Due to the large leakage current, the image of the hysteresis loop presents an inclined ellipse, which is similar to previous reports. It can be seen that BFO-3 still has ferroelectric properties at room temperature.

[0019] Bi2Fe4O9 materials have attracted much attention in the field of visible light photocatalysis due to their non-toxicity, chemical stability, and ability to absorb light from ultraviolet to visible light. From the perspective of photocatalysis, as an excellent photocatalyst, the magnetism of Bi2Fe4O9 exhibits paramagnetism or weak ferromagnetism at room temperature, which is not conducive to the recycling of Bi2Fe4O9 photocatalysts. If ferromagnetic materials are simply compounded on Bi2Fe4O9 monomers, it may not only limit the catalytic efficiency of Bi2Fe4O9 monomer materials, but also be detrimental to the further modification of Bi2Fe4O9. Based on this, the strong ferromagnetic Bi2Fe4O9 we invented can change this situation.

[0020] In addition, the Bi2Fe4O9 material of the present invention has both ferromagnetism and ferroelectricity at room temperature, and has the possibility of simultaneously manipulating electrical and magnetic properties. Therefore, it has great application potential in spin electronic devices, sensors and digital storage devices.

[0021] In summary, the present invention discloses a new method, which induces Bi2Fe4O9 to exhibit strong ferromagnetism at room temperature by introducing NaBH4. A series of characterization data show that the material is still pure single-phase Bi2Fe4O9, accompanied by a large number of missing Bi atoms. In addition, the present invention also proposes a possible mechanism of the source of magnetism. Moreover, this interesting phenomenon of strong ferromagnetism Bi2Fe4O9 has never been reported before. We hope that this new discovery can improve people's understanding of the magnetism of this material, and at the same time provide new ideas for the photocatalytic recovery application and multiferroic research of this material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 (a) XRD patterns of BFO-3, BFO-3a, and BFO-3b; (b) XRD local magnified images of BFO-3, BFO-3a, and BFO-3b.

[0023] Figure 2 SEM images of samples prepared in the present invention; (a) BFO, (b) BFO-3.

[0024] Figure 3 XPS spectra of BFO, BFO-1, BFO-2, and BFO-3. (a) Fe2p, (b) O1s, (c) Bi4f.

[0025] Figure 4(a) Structural diagram of Bi2Fe4O9, where the arrows represent the spin directions. (b) Raman scattering spectra of BFO and BFO-3. (c) Schematic diagram of the frustrated spin Cairo pentagon.

[0026] Figure 5 (a) MH hysteresis loops of BFO, BFO-1, BFO-2, and BFO-3, where the inset in the lower right corner is an enlarged MH diagram of BFO; (b) MH curves of BFO, BFO1, BFO-2, and BFO-3 near H=0.

[0027] Figure 6 This is the hysteresis loop of the BFO-3 sample of the present invention at room temperature and 1 kHz. DETAILED DESCRIPTION

[0028] The present invention is further explained below with reference to specific embodiments. Example

[0029] Step 1: Preparation of Bi2Fe4O9 nanosheets. First, 2.0613g of Bi(NO3) •5H2O and 1.3515g of FeCl3•6H2O were dissolved in 50ml of ethylene glycol solution with a volume concentration of 50% under magnetic stirring, and then 200ml of deionized water was added, and the pH was adjusted to 11 by dropping concentrated ammonia water. The obtained brown precipitate was washed with deionized water, added to 40ml of 14mol / L NaOH solution, and after sufficient stirring, the sample was transferred to a 100ml autoclave and sealed. After hydrothermal treatment at 180℃ for 72h, the sample was ultrasonically treated with 2mol / L nitric acid for 30min to remove impurities, and finally washed repeatedly with deionized water and ethanol at 70 o C and dried. We named the prepared Bi2Fe4O9 nanosheets BFO.

[0030] The second step is Bi2Fe4O9 modification. First, 0.05 mol of BFO and NaBH4 (1:1) were fully ground in an agate mortar until a uniform mixture was formed and loaded into a porcelain boat. Then, after calcining in a tube furnace (300℃, 400℃) with argon for 1 hour, the obtained sample was washed with deionized water and ethanol. Then, 2 mol / L nitric acid was used to remove impurities by ultrasound for 30 minutes, and finally, it was repeatedly washed with deionized water and ethanol and dried at 70℃. We named the samples obtained at 300℃ and 400℃ BFO-1 and BFO-2 respectively; the sample obtained at 400℃ with a ratio of 0.05 mol BFO ​​and 0.075 mol NaBH4 (1:1.5) was named BFO-3. Under the same experimental conditions, the sample that was not washed with nitric acid after calcination was named BFO-3a, and the sample without NaBH4 was named BFO-3b.

[0031] For structural characterization and performance evaluation, see above.

Claims

1. A method for preparing a strong ferromagnetic Bi2Fe4O9 material at room temperature, characterized in that: The following steps are involved: 1) Preparation of Bi2Fe4O9 nanosheets: Bi(NO3) •5H2O and FeCl3•6H2O were dissolved in ethylene glycol solution, and then deionized water was added to mix. The pH was adjusted to 11.0±0.2 with concentrated ammonia solution. After precipitation was complete, the precipitate was washed to neutrality and then added with 13~15mol / L NaOH solution and stirred evenly until there were no lumps. After hydrothermal treatment at 170~190℃ for 48~72h, the precipitate was acid-washed to remove impurities, washed and dried to obtain Bi2Fe4O9 nanosheets, named BFO; 2) Modification of Bi2Fe4O9: Grind and mix BFO and NaBH4 evenly, put them into a porcelain boat, and then heat them to 300~400℃ in a tubular furnace with argon gas and calcine them for 1~2h. Then, pickle the obtained sample to remove impurities, wash and dry it to obtain modified Bi2Fe4O9.

2. A method for preparing a strong ferromagnetic Bi2Fe4O9 material at room temperature as claimed in claim 1, characterized in that: In step 1), the molar ratio of Bi(NO3)•5H2O to FeCl3•6H2O is 0.75:1-0.85:

1.

3. A method for preparing a strong ferromagnetic Bi2Fe4O9 material at room temperature as claimed in claim 1, characterized in that: In step 1), the volume ratio of the ethylene glycol solution to deionized water is 1:3 to 1:

5.

4. A method for preparing a strong ferromagnetic Bi2Fe4O9 material at room temperature as claimed in claim 1, characterized in that: In step 2), the molar ratio of BFO to NaBH4 is 1:1 to 1:1.

5.

5. A room temperature ferromagnetic Bi2Fe4O9 material prepared by the method of claim 1, characterized in that: M S =10.22 emu / g, M r =2.93 emu / g。